THE WRITING PATHS OF REFLECTIVE TEACHERS: TEACHING AUTHORITY AND RECORDS THROUGH FORM DIARIES (ACTIVE) IN A COLLABORATIVE NETWORK - Mara de Sousa Lapa Cunha, Rúbia; Oliveira Silva, Fabrício (Revista Gênero e Interdisciplinaridade, 2024)
This article tried to investigate the contributions of writing reflective diaries for basic education teachers in the microregion of Jacobina under the eyes and sensitive listening in an action of productions authorized or not, in the records and/or signs/notes, in the activities in which referred to the preparation of training diaries (field, memorial, experiences and practices) that were to be characterized in a movement of (re)thinking didactic situations and or intervention projects or professional master’s project to be configured in a cycle of reflection and redesign of their wanderings and teaching paths. Therefore, I focused on the data that were collected through questionnaires with open questions with the intention of understanding how teachers perceive themselves in this path of knowledge and experiences constructed and (re)elaborated. The data analysis showed that the students recorded the events in the notebook, demarcating their daily routines and from the perspective of a diary, immediately after the formalization of the knowledge projected in a space in the pedagogical notebook and/or notebook that depended on the school or the public sphere of activity. municipal or state. However, some carried out a detailed description of them without any “privilege” or appreciation of this route. Even so, the act of writing or doodling the praxis went beyond what was initially intended by most teachers/students or “lay” teachers, teachers considered “multipurpose” based on the distribution of the workload. The entire process of writing in class diaries or teaching plans and action plans gave us the opportunity to understand the reflection of a practice observed and aligned in one’s own daily practice. It is important to mention that the entire didactic/pedagogical action was configured as a support to memory and enabled an “apparent” distance from lived experiences, allowing for a more dense analysis of these based on the formalization of knowledge in a specific research space. which we call Training Diary. Furthermore, the importance of the Teacher/trainer offering feedback, oral or written, and reflection on the reworking of the instruments used to signal events was highlighted, being systematized in a training agenda with pre-established tracks in the theoretical framework linked to a paradigm of research/action.